Studies in symbolic interaction. Vol. 37 - Denzin, Norman K.; Faust, Ted. (Bingley, U.K. : Emerald, 2011)
Volume 37 in the bi-annual series Studies in Symbolic Interaction is divided into three distinct parts: Part One, Theoretical Openings, focuses on new theoretical work in the interactionist tradition by leading interdisciplinary scholars. It examines the mesodomain of welfare reform through re-negotiating the order of economic inequality, provides a grounded fractal analysis into the medicalization of homelessness and the sociology of the self, and looks at the labeling of immigrant men as criminals. In Part Two, Studies in Social Construction, focus shifts to issues of gender, ethnicity, illness and the urban situation including articles on the social constructions of the non-prejudiced white self, womens interaction with romantic comedies and the impact on their relationship, and engaging cultural narratives of the ethnic restaurant. The third and final part, Autoethnographic Interventions, turns inward to autoethnographic reflections on identity, technology, family, work and self including contributions on the digital evolution of an American identity and nursings moral imperative as the flexible professional and the discourse of unexpected evidence.
Fort Davis national historic site : an Indian fort without Indians / Robert Pahre -- The medicalization of homelessness and the sociology of the self : a grounded fractal analysis / Jason Adam Wasserman, Jeffrey Michael Clair -- Interethnic interactions and perceptions of immigrant men in public space : the experience of community safety by seniors in a multicultural neighbourhood / Thaddeus M$1#7H(Bler -- Parenting a youthful offender / Jane C. Hood -- Review of the social history of language and social interaction research : people, places, ideas by Wendy Leeds-Hurwitz / Andrew P. Carlin -- Social constructions of the nonprejudiced white self / Shannon K. Carter, Fernando I. Rivera -- Engaging cultural narratives of the ethnic restaurant : discursive practices of hybridity, authenticity, and commoditization / Robin Patric Clair, Isaac Clarke Holyoak, Theon E. Hill, Prashant Rajan, Elizabeth L. Angeli, Melissa L. Carrion, Sydney Dillard, Rati Kumar, Shaunak Sastry -- Illness metaphors, Japan's'Gaijin' race philosophy, and the formation of the self / Sheri Bell -- Women's interactions with romantic comedies and the impact on their relationships : happily ever after / Nicolette Caperello, Todd Migliaccio -- The digital evolution of an American identity / C. Waite Phelan -- The rhetorical negotiation of professional identity : nursing's moral imperative as the flexible professional and the contribution of unexpected evidence / Robin Patric Clair, Rebekah L. Fox.s
Keywords: Symbolic interactionism